The Molecular Weight of Enzymatically Modified Pectic Oligosaccharides from Apple Pomace as a Determinant for Biological and Prebiotic Activity - Agnieszka Wilkowska; Adriana Nowak; Ilona Motyl; Joanna Oracz (Molecules)
The purpose of this research was to investigate the prebiotic effects of different fractions of pectin-derived oligosaccharides (POSs) from apple pomace (AP) in relation to their molecular weight (MW), structure, and composition. Enzymatic treatment of the apple pomace resulted in high-molecular-weight arabinans and rhamnogalacturonans (MW 30–100 kDa, MW 10–30 kDa), as well as oligomeric fractions with molecular weights of less than 10 kDa, consisting mainly of homogalacturonan. The biological potential of the POSs against various lactobacilli and bifidobacteria was evaluated. The oligosaccharides with the highest molecular weights (MW 30–100 kDa, MW 10–30 kDa) showed better prebiotic effect to lactobacilli. The oligosaccharides with MW 3–10 kDa and MW 10–30 kDa caused an increase in the bifidogenic effect. Inhibition of Escherichia coli, Salmonella enterica serovar Typhimurium, and Listeria monocytogenes was also observed. The preparations with MW 3–10 kDa and MW 10–30 kDa demonstrated the strongest biological activity, supporting the adhesion of beneficial microorganisms to mucin and collagen surfaces. Therefore, oligosaccharides with MW 10–30 kDa were considered to be the most promising prebiotic candidates. This study confirms that the biological effects of pectic oligosaccharides vary significantly based on their structural differences. Therefore, the conditions of enzymatic hydrolysis of apple pectin should be optimized to obtain oligosaccharides within a specific molecular mass range.